Keterkaitan Antara Kontrol Diri Dengan Empati Pada Siswa Kelas VII SMP Negeri 2 Sragen - Natasya Odelia; Dhian Rizkiana Putri (Khatulistiwa: Jurnal Pendidikan dan Sosial Humaniora, 2024)
Self-control is an individual's ability to restrain momentary desires or urges that conflict with behavior that is not in accordance with social norms. Adolescents who have low self-control will also have a low sense of empathy and will not think about the long-term effects of the behavior they have carried out. Empathy is an activity to understand what other people are thinking and feeling, as well as what other people are thinking and feeling. This research aims to determine the relationship between self-control and empathy in class VII students at SMP Negeri 2 Sragen. The research method used in this research is a quantitative method. The population in this study were students of SMP N 2 Sragen, while the sample in this study was class VII students of SMP N 2 Sragen with a total of 198 students as respondents. The results of hypothesis testing show that the hypothesis proposed in this research cannot be accepted, as evidenced by the absence of a significant or strong relationship between empathy and self-control in class VII students at SMP N 2 Sragen. This can be seen in the correlation test results obtained with a value of r = 0.318, with a significance of p = 0.818.